Critical Analysis of Healthcare Technology Integration, Patient Empowerment, and Cost Efficiency - Alqarni, Bader Ayed Alqarni; kurdi, Noorah Samir; Alelyani, Jaber fayez Mohammed; Almutairi, Abdulrazaq Mulfi; Alshehri, Ahmed Mohammed Ali; Almansour, Nasser Muidh Ali; Alqarni, Mohammed Ayed; Alshehri, Mona Abdulrahman Mohammed; Alamri, Norah Ayed; Alamri, Reem Salman Hassan (Journal of Ecohumanism, 2024)
This paper examines the role of Healthcare Technology in patients’ involvement and determining cost efficiency in healthcare delivery. This critically examines how the technological advancement in the healthcare industry, e.g., EHR, telemedicine and AI, are transforming one’s care, enhancing quality, and lowering costs. Also, the paper describes the role of patient self-management-support, including using digital solutions, knowledge, and involvement in enhancing health and resource management in practice. The last section describes the costs and revenue that might be gained from technology in the center and the main issue of integrating innovation with restraint in technology investment.